PEER SUPPORT IN PSYCHOSOCIAL RECOVERY: A QUALITATIVE STUDY OF NAPZA (SUBSTANCE USE DISORDERS) REHABILITATION AT THE RUMOH GEUTANYOE ACEH FOUNDATION - Amalia, Wirda; Tanjung, Wardah Septiani; Sulong, Jasni Bin (Jurnal Al-Ijtimaiyyah, 2026)
Peer support is widely recognized as a key component in the recovery of individuals with substance use disorders (SUD), yet its role in community-based rehabilitation within socio-religious such as in Aceh contexts remains underexplored. This study examines the contribution of peer support and its psychosocial impacts at the Rumoh Geutanyoe Aceh Foundation. Using a descriptive qualitative approach, data were collected through observation, in-depth interviews, and documentation involving eight informants (four active clients, two peer counselors, one former client and one coordinator program) and analyzed using Miles and Huberman’s interactive model. The findings indicate that peer support significantly enhances psychosocial recovery by strengthening motivation, self-confidence, and resilience. This process is reflected in key dimensions of social support—particularly reassurance of worth, guidance, and reliable alliance—through emotional bonding, shared experiences, and sustained mentoring relationships. Peer support also fosters a stigma-free and supportive environment that promotes long-term recovery. This study contributes to the limited literature on peer-based rehabilitation in local and Islamic socio-cultural contexts and highlights the importance of integrating peer support into community-based recovery programs.